Proud to Belong: The Impact of Ethics Training on Police Officers in Ghana - Donna Harris; Oana Borcan; Danila Serra; Henry Telli; Bruno Schettini; Stefan Dercon (Institute of Labor Economics (IZA), 2024)
We examine the impact of ethics and integrity training on police officers in Ghana through a randomized field experiment. The program, informed by theoretical work on the role of identity and motivation in organizations, aimed to re-activate intrinsic motivations to serve the public, and to create a new shared identity of "Agent of Change." Data generated by an endline survey conducted 20 months post training, show that the program positively affected officers' values and beliefs regarding on-the-job unethical behavior and improved their attitudes toward citizens. The training also lowered officers' propensity to behave unethically, as measured by an incentivized cheating game conducted at endline. District-level administrative data for a subsample of districts are consistent with a significant impact of the program on officers' field behavior in the short-run.
Keywords: H76; K42; M53; D73; 330; ethics training; traffic police; experiment